The Maternal and Child Health Handbook for Improving the Continuum of Care and Other Maternal and Child Health Indicators in Angola: An Implementation Study Protocol - Aoki, Ai; Mochida, Keiji; Kuramata, Michiru; Sadamori, Toru; Freitas, Helga Reis; da Cunha, João Domingos; Sapalalo, Pedro; Tchicondingosse, Lino; Balogun, Olukunmi Omobolanle; Hiraoka, Hisakazu; Aiga, Hirotsugu; Takehara, Kenji (Frontiers in Global Women's Health, 2021)
Background: Reducing maternal, neonatal, and infant mortality tops the health targets of sustainable development goals. Many lifesaving interventions are being introduced in antenatal, delivery, and postnatal care. However, many low- and middle-income countries (LMICs) have not reached maternal and child health targets. The Maternal and Child Health Handbook (MCH-HB) is recommended as a home-based record to promote a continuum of care from pregnancy to early childhood, and is gaining increasing attention among LMICs. Several countries have adopted it as national health policy. To effectively utilize the MCH-HB in LMICs, implementation needs to be considered. Angola is an LIMC in Sub-Saharan Africa, where maternal and child health indicators are among the poorest. The Angolan Ministry of Health adopted the MCH-HB program in its national health policy and is currently conducting a cluster randomized controlled trial (MCH-HB RCT) to evaluate its impact on the continuum of care. This study aimed to evaluate implementation status, and barriers and facilitators of MCH-HB program implementation in Angola. Methods: To evaluate implementation status comprehensively, the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) framework will be used. Four components other than effectiveness will be investigated. A cross-sectional survey will be conducted targeting all health facilities and officers in charge of the MCH-HB at the municipality health office in the intervention group after the MCH-HB RCT. Data from the cross-sectional survey, secondary MCH-HB RCT data, and operational MCH-HB RCT records will be analyzed. Health facilities will be classified into good-implementation and poor-implementation groups using RE-AIM indicators. To identify barriers to and facilitators of MCH-HB implementation, semi-structured interviews/focus group discussions will be conducted among health workers at a sub-sample of health facilities and all municipality health officers in charge of MCH-HB in the intervention group. The Consolidated Framework for Implementation Research will be adopted to develop interview items. Thematic analysis will be performed. By comparing good-implementation and poor-implementation health facilities, factors that differ between groups that contribute to successful implementation can be identified. Discussion: This study’s findings are expected to inform MCH-HB implementation policy and guidelines in Angola and in other countries that plan to adopt the MCH-HB program.